(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
The process of deep drawing of complex shapes is a difficult process compared to the process of drawing simple shapes such as cylindrical, square and rectangle because of the complex shape is subjected to the higher stresses concentration compared to simple shapes. This work aims to study the effect of the wall corner radius of punch and radial clearance on deep drawing operation using the experimental work and numerical simulation. In this work, an analysis of the deep drawing process is performed for process design of stellar cup drawing. A deep drawing die was designed and manufacturing to perform the experimental procedure required to produce a stellar cup with inner dimensions (major axis equal to 43.7 mm and minor axis equal to 36.64 mm) formed from a circular flat sheet (80 mm diameter) comprised of low carbon steel of (0.08%) carbon content, without any intermediate annealing. A commercially finite element program code (ANSYS 18.0) is utilized to simulate the stellar deep drawing operation. From the comparison between the results, it has been found that the thinning at cup corner increases by decreasing the wall corner radius of the punch and the maximum thinning with the wall corner radius of the punch equal to ( 16Rcp’> = 2 mm) at the corner of the minor axis of completely drawn cup